1983
DOI: 10.3382/ps.0622017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Fat and Tocopherol on Lipolysis and Oxidation in Turkey Meat Stored at Different Temperatures

Abstract: Turkeys were fed diets containing tallow or soybean oil with either 5 or60mg/kg all-rac-a-tocopherol for 9 weeks before slaughter. Muscle was sampled aseptically from breast or thigh and stored at 37, 4, or -18 C.Tocopherol tissue content reflected dietary levels; the fatty acid composition of muscle triglycerides was significantly affected by the dietary fat but that of phospholipids was influenced only slightly by the different diets.Both oxidative and lipolytic changes were greater in leg muscle than in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
5
27
0
Order By: Relevance
“…Sklan et al (1983) reported that increased dietary a-tocopherol concentrations resulted in increased a-tocopherol content and decreased oxidation of turkey meat during storage at 4°C and -18°C. Sheehy et al (1993) showed that incorporation of a-tocopherol into chicken muscles significantly improved the oxidative stability of raw muscle during frozen storage and cooked muscle during both refrigerated and frozen storage.…”
Section: Lipid Oxidation In Burgersmentioning
confidence: 98%
“…Sklan et al (1983) reported that increased dietary a-tocopherol concentrations resulted in increased a-tocopherol content and decreased oxidation of turkey meat during storage at 4°C and -18°C. Sheehy et al (1993) showed that incorporation of a-tocopherol into chicken muscles significantly improved the oxidative stability of raw muscle during frozen storage and cooked muscle during both refrigerated and frozen storage.…”
Section: Lipid Oxidation In Burgersmentioning
confidence: 98%
“…Precooked products made from turkey meat are most susceptible to WOF, followed closely by chicken, pork, beef and mutton (Wilson, Pearson, & Shorland, 1976). Low stability of turkey meat is due to the high amount of polyunsaturated fatty acids (Mercier, Gattellier, Viau, Remingnon, & Renerre, 1998;Pearson et al, 1977), and relatively low levels of natural tocopherols (Sklan, Tenne, & Budowski, 1983). The oxidation of unsaturated fatty acids in turkey meat leads to the formation of many volatile compounds that could be associated with WOF (Ruenger, Reineccius, & Thompson, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…However, a high degree of polyunsaturation accelerates oxidative processes leading to deterioration in meat flavor, color, texture and nutritional value. Turkey meat is particularly prone to oxidation due to its high PUFA content (Mercier, Gattellier, Viau, Remingnon, & Renerre, 1998), its high concentration in free iron (Kanner, Hazan, & Doll, 1988) and due to the turkey's low ability to store dietary vitamin E (Sklan, Tenne, & Budowski, 1983).…”
Section: Introductionmentioning
confidence: 99%